Sustainable Energy : Towards a Zero-Carbon Economy Using Chemistry, Electrochemistry and Catalysis - Ross, J. R. H. (Elsevier, 2022)
"Sustainable Energy, Towards a Zero-Carbon Economy Using Chemistry, Electrochemistry and Catalysis provides the reader with a clear outline of some of the strategies, particularly those based on various chemical approaches, that have been put forward with the aim of reducing greenhouse gas emissions in order to achieve "zero carbon" by 2050. The author describes the chemistry of some of the processes involved, paying particular attention to those that involve heterogeneous catalytic steps and electrolysis methods. In cases in which the technology is already established, details are given of the reactor systems used. He discusses novel developments in the areas of transport, the production of essential products using renewable energy and the uses of sustainable biomass" --